What makes a long tail short? Testing Allen's rule in the toque macaques of Sri Lanka - Huffman, M.A.; Kumara, R.; Kawamoto, Y.; Jayaweera, P.M.; Bardi, M.; Nahallage, C.A.D. (Wiley, 2020)
Allen's rule (1877) predicts ecogeographical anatomical variation in appendage proportions as a function of body temperature regulation. This phenomenon has been tested in a variety of animal species. In macaques, relative tail length (RTL) is one of the most frequently measured appendages to test Allen's rule. These studies have relied on museum specimens or the invasive and time‐consuming capturing of free‐ranging individuals. To augment sample size and lessen these logistical limitations, we designed and validated a novel noninvasive technique using digitalized photographs processed using LibreCAD, an open‐source 2D‐computer‐aided design (CAD) application. This was used to generate pixelated measurements to calculate an RTL equivalent, the Tail to Trunk Index (TTI) = (tail [tail base to anterior tip] pixel count/trunk [neck to tail base] pixel count). The TTI of 259 adult free‐ranging toque macaques (Macaca sinica) from 36 locations between 7 and 2,087 m above sea level (m.a.s.l.) was used in the analysis. Samples were collected from all three putative subspecies (M. s. sinica, aurifrons, and opisthomelas), at locations representing all altitudinal climatic zones where they are naturally distributed. These data were used to test whether toque macaque tail length variation across elevation follows Allen's rule, predicting that RTL decreases with increasing elevation and lower temperature. Our results strongly supported this prediction. There was also a statistically significant, negative correlation between elevation and annual average temperature. The best predictor for the TTI index was elevation. Significant subspecies differences in RTL are linked in part to their ecological and altitudinal niche separation, but overall the variation is seen as the species' adaptation to climate. The method developed for the quick morphometric assessment of relative body proportions, applicable for use on unhabituated free‐ranging animals, widens the range of materials available for research studying morphological characteristics and their evolution in primates
Keywords: Allen's rule, elevation, morphometrics, Sri Lanka, tail length, toque macaque